The breeding and maintenance of sledge dogs - Taylor, R. J. F. (Polar Record, 1957)
One of the logical reasons for exploration is to collect the maximum of information in a specified time; therefore planning should be based on an appreciation of the pregnable gaps in as many fields of science as possible. Present Antarctic exploration is neglecting the biological sciences and in particular those of an experimental nature. Figures published for the contingents from the British Commonwealth, France and Norway at present in Antarctica include twenty-three physicists, thirteen geologists of different varieties and only two biologists. This neglect probably arises from a too rigid conception that field biology is concerned with classification and with natural history. Antarctica, however, offers great possibilities, and even certain advantages, for much biological work, and in particular its simplicity helps ecological thought and nutritional experimentation.